Return on investment of near-shoring projects - Guedes, J. F. (2021)
The Information Technology sector has been using proximity offshoring (near-shoring) as common practice over the past 2 decades, mainly for software development projects. Using a large business transformation project from a global consumer goods company as a single case study, the present paper analyses the benefits and key challenges of incorporating such delivery models in these types of projects, focusing its attention mainly on the financial and quality aspects. The analysis suggests that, when compared to traditional services delivery (on-site consultants), near-shoring practices can have a very positive financial impact for the vendor and the customer, translating into an increase on the Return on Investment (ROI) without a significant increase of risks or losses in quality – The project’s cost can have a significant reduction on the vendor side, with a consequent reduction to the end client. Regardless these benefits, it is suggested that traditional consulting still plays an un-replaceable role in these types of projects. Furthermore, it is suggested that it is equally important the commitment from top management for such initiatives.